A new dwarf forest toad (Amphibia: Bufonidae: Nectophrynoides) from the Ukaguru Mountains, Tanzania - Menegon, Michele; Salvidio, Sebastiano; Ngalason, Wilirk; Loader, Simon P. (Zootaxa, 2007)
A new species of Nectophrynoides from the Ukaguru Mountains, Eastern Arc Mountains Tanzania, is described. The new species is diagnosed by the presence of large prominent spines with keratinized tips, positioned on the dorsum, head and limbs. In addition, the combination of the following characters presence of large tympanum and annulum, foot longer than tibia, the lack of parotoid glands and advertisement call features, allow this species to be distinguished from all other species in the genus. The new species adds to our understanding of the relatively undersampled and poorly understood, amphibian fauna of the Ukaguru Mountains.